30-year recovery rate of timber volume and aboveground carbon density in different felling intensities - Saleh @Japri, Mohd Nazre; Richard, Aldrich; Burslem, David; Kettle, Christopher J. (Forestry Department of Peninsular Malaysia, 2024)
Defining harvesting regimes for sustainable forest management is important for sustainable timber production and mitigation of climate change. Implementing sustainable forest management strategies that will contribute to these benefits will require an understanding of logging effect on tree growth and forest recovery. In this paper, we analysed the long-term growth of tropical forests logged under the Selective Management System in Peninsular Malaysia to understand how management regimes affected timber yield and carbon sequestration including the actual recovery rates. The management regimes employed were unlogged, moderately logged and intensely logged. This study showed that there was no difference in total timber volume and aboveground carbon density one year post-logging between logging intensities. The recovery rate of timber volume and aboveground carbon density varied significantly between plots with different management regimes. Intensely logged forests had a higher rate of recovery for timber volume (1.85 m3 ha-1 yr-1, CI: 1.65 to 2.02) and aboveground carbon density (1.65 tonnes C ha-1 yr-1, CI: 1.46 to 1.82). However, these long-term recovery rates were lower than the national average which will affect the supply of sustainable timber and carbon sequester from logged-over forests. The cutting cycle of 30 years that is built into the Selective Management System will not be sufficient for the recovery of logged-over forests to pre-logging status.